Tension Type Headache Comorbid with Moderate Depression: A Case Report - Budi Pratiti (Scientia Psychiatrica, 2020)
Tension type headaches (TTH) are generally caused by psychological factors and psychiatric disorders. Anxiety disorders and depression are more often associated with TTH than other disorders. This case report discusses the tension type headache accompanied by depression and its management. Miss Y, a 17 year old girl, 2nd in birth order, an undergraduate student living in a boarding house with her sister and coming from a low socio-economic background, came to Dr. Sardjito General hospital, Indonesia with complaints of severe headache since 2 months ago. Family history shows that there is a conflict in the patient's parents which makes the patient disappointed. In the examination found inferiority feelings, guilt and worry will disappoint everyone. She was then agreed to do cognitive behavior therapy and take medication according to doctor's orders. After 8 sessions, she developed confidence and started to carry out daily similar sessions at home. Tension-type headache in this case is accompanied by a dominant psychological factor. Collaboration between pharmacotherapy and psychotherapy in treating patients with tension type headaches is a fairly effective choice.